SEATED SALINE SUPPRESSION TESTING FOR THE DIAGNOSIS OF PRIMARY ALDOSTERONISM. A VALIDATION STUDY. (June 2018) - Stowasser, M.; Ahmed, A.; Cowley, D.; Wolley, M.; Mcwhinney, B.; Ungerer, J.; Gordon, R.D.
Abstract: Objective: Primary aldosteronism (PA) is confirmed by failure of plasma aldosterone (aldo) suppression during fludrocortisone (FST) or saline suppression testing (SST). Aldo can be higher upright (e.g. seated) than recumbent in PA; upright levels are used during FST. We hypothesized that seated SST (SSST) is more sensitive than recumbent (RSST). In our pilot study of 24 patients with confirmed PA, 23 tested positive by SSST compared to 8 by RSST (JCEM2014;99:2745–53). The current validation study involved 100 patients who underwent FST, RSST and SSST, eight of them both before and after unilateral adrenalectomy. Of the 108 FSTs, 94 were performed on hypertensives with raised aldo/renin ratios to confirm/exclude suspected PA (PreADX), and 14 on patients following adrenalectomy for previously diagnosed unilateral PA to confirm/exclude cure (PostADX). For SSTs, aldo was measured basally at 8am and after 2 L normal saline infused over 4 h in either the seated or recumbent position. Of the 108 FSTs, 73 confirmed PA, 17 excluded PA and 18 were inconclusive. Four patients with inconclusive FST lateralized on adrenal venous sampling (confirming unilateral PA), making a total of 77 with PA. Among the 84 patients with conclusive FST, SSST and RSST results, ROC analysis established optimal cut-off aldo levels of 163 pmol/L for SSST and 105 pmol/L for RSST. At these cut-offs, SSST showed much greater sensitivity than RSST (87 vs 41%; p = 0.012) but similar specificity (94 vs 100%; NS). The area under the ROC curve was greater for SSST than RSST (0.96 ± 0.02 SE vs 0.81 ± 0.06; p < 0.01). Of 28 patients with unilateral PA, 26 (93%) were positive, one negative and one inconclusive by SSST, while 20 (71%) were positive, six negative and two inconclusive by RSST. Of 43 with bilateral PA, 36 (84%) were positive, six negative and one inconclusive by SSST, while only 8 (19%) were positive, 32 negative and three inconclusive by RSST. Of 17 with PA excluded by negative FST, 16 (94%) were negative and one positive by SSST and 16 (94%) were negative and one inconclusive by RSST. Among the entire set of 108 studies performed, only three SSST (vs 9 RSST and 18 FST) results were inconclusive. SSST is much more sensitive than RSST, has a similar low false positive rate, and has a lower proportion of inconclusive results than either RSST or FST. It therefore offers a reliable and much less complicated and expensive alternative to FST for the confirmation of PA.